Co-expression of Stem Cell Markers CD133 and CD44 as Predictors of Metastatic Potential of Colorectal Carcinoma - Kostovski, Ognen; Jovanovikj, Rubens; Kostovska, Irena (Turkish Surgical Society and Turkish Surgical Community, 2025)
Objective: One of the most prevalent cancers in the world is colorectal carcinoma (CRC). Aggressive cancer forms and a poor prognosis are linked to cancer stem cell (CSC) markers. The study aimed to determine whether the co-expression of the CSC markers CD133 and CD44 could predict an increased risk of metastasis in colorectal cancer. Material and Methods: Our study included 90 patients with CRC. All patients were divided into two subgroups: Metastatic CRC and non-metastatic CRC. Initially, tumor samples were examined using conventional histological techniques, and then immunohistochemical analysis with monoclonal antibodies against CD133 and CD44 markers was performed. Results: High co-expression of CD133 and CD44 was observed in 71.4% of patients with metastatic disease, compared to 37.9% in patients without distant metastases. Discordant expression of both markers was found in 8% of the subgroup with metastatic CRC and 13.4% of the subset without metastatic CRC. Statistical analyses showed a significant association of increased expression of CD133 and CD44 with the disease stage, T- category, and N- nodal status. With multiple regression analysis, the stage of disease was singled out as the factor with the greatest and statistically significant influence on the expression of CD133 (p<0.0001) and CD44 (p<0.0001). Conclusion: Co-expression of CD133 and CD44 plays an essential role in predicting the metastatic form of CRC. Both stem cell markers can be implemented in standard pathohistological diagnostics and can be useful markers for pre-therapeutic oncology screening.
Keywords: Colorectal carcinoma; stem cells; CD133+; CD44+; metastatic potential